2008
DOI: 10.1159/000140453
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Vinorelbine versus Docetaxel for Metastatic Breast Cancer after Failing Anthracycline Treatment

Abstract: Background: Vinorelbine and docetaxel are active in anthracycline-pretreated, metastatic breast cancer. We compared their efficacy. Patients and Methods: Patients were randomized to receive weekly vinorelbine (VIN) or weekly docetaxel (DOC), 6 weekly doses per 8-week cycle, with optional crossover (X-DOC vs. X-VIN. The primary end point was time to progression (TTP) on initial treatment. Remission induction, survival, and quality of life were secondary end points. Results: Among 122 poor risk patients, a non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
5
5
1
Order By: Relevance
“…The patients randomized in this study were relatively heavily pretreated with the majority having received 2-3 lines of prior treatment for their metastatic disease. The lower response rates with vinorelbine as compared to docetaxel in this study concur with results reported in other studies [16]. However, the numbers in both this study and the other unselected study [16] are small and need to be interpreted with caution.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The patients randomized in this study were relatively heavily pretreated with the majority having received 2-3 lines of prior treatment for their metastatic disease. The lower response rates with vinorelbine as compared to docetaxel in this study concur with results reported in other studies [16]. However, the numbers in both this study and the other unselected study [16] are small and need to be interpreted with caution.…”
Section: Discussionsupporting
confidence: 90%
“…The lower response rates with vinorelbine as compared to docetaxel in this study concur with results reported in other studies [16]. However, the numbers in both this study and the other unselected study [16] are small and need to be interpreted with caution. With regard to toxicity, in the present study, grade 3-4 hematological adverse events and infection were tenfold greater with docetaxel as compared with vinorelbine, consistent with results in HERNATA [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, this network, based on step 1, only allowed for an indirect comparison of everolimus (plus hormonal therapy) to the chemotherapies CD and CMF. Since these chemotherapy combinations were not of interest, the network was extended to include an additional 14 RCTs comparing alternative chemotherapies of interest [41,42,45-47,49,50,54,57-60,63],[65,66]. …”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, vinorelbine as a single agent was compared with taxane alone in four trials , with capecitabine alone in two trials , with 5‐FU/LV and FAMtx (mitoxantrone, 5‐fluorouracil and leucovorin.) in one trial , and with a vinorelbine‐combined regimen in another trial .…”
Section: Resultsmentioning
confidence: 99%